The Homelanders: The Long Way Home - Book 2 - Klavan, Andrew (Nashville, Tenn. : Thomas Nelson, 2010)
As eighteen-year-old Charlie West continues to elude the law and the group of terrorists looking for him, he tries to remember what happened a year ago and find out who has framed him so he can clear his name.
Keywords: Amnesia -- Fiction; Terrorism -- Fiction; Fiction